PENGARUH DAYA TARIK IKLAN DAN POTONGAN HARGA TERHADAP PEMBELIAN IMPULSIF TIKTOK SHOP DI FAKULTAS EKONOMI UNIVERSITAS KRISNADWIPAYANA - Alya Febi Triwinarti; Arry Dwi Syahputra (Jurnal Ekonomi dan Industri, 2025)
This study aims to determine the effect of advertising appeal and discounts on impulsive purchases at TikTok Shop at the Faculty of Economics, Krisnadwipayana University. This research is included in the category of associative research using a quantitative approach. The population of this study were users of Tiktok Shop, Faculty of Economics, Krisnadwipayana University. The sampling technique in this study was carried out using the accidental sampling method. Analyzed using simultaneously and partially linear regression methods. The results of the study indicate that simultaneously and partially the appeal of advertising and discounts have a positive and significant effect on impulsive purchases of Tiktok Shop, Faculty of Economics, Krisnadwipayana University.